Emerging Technologies Adoption in Airports - AlNoman, Hassan Abdalla (2025)
A Master of Science thesis in Engineering Systems Management by Hassan Abdalla AlNoman entitled, “Emerging Technologies Adoption in Airports”, submitted in April 2025. Thesis advisor is Dr. Noha Mohamed Hassan Hussein and thesis co-advisor is Dr. Zied Bahroun. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).